What are snow leopards really eating? Identifying bias in food‐habit studies - Sarah R. Weiskopf; Shannon M. Kachel; Kyle P. McCarthy (Wildlife Society Bulletin)
ABSTRACT Declining prey populations are widely recognized as a primary threat to snow leopard (Panthera uncia) populations throughout their range. Effective snow leopard conservation will depend upon reliable knowledge of food habits. Unfortunately, past food‐habit studies may be biased by inclusion of nontarget species in fecal analysis, potentially misinforming managers about snow leopard prey requirements. Differentiation between snow leopard and sympatric carnivore scat is now cost‐effective and reliable using genetics. We used fecal mitochondrial DNA sequencing to identify scat depositors and assessment bias in snow leopard food‐habit studies. We compared presumed, via field identification, and genetically confirmed snow leopard scats collected during 2005 and 2012 from 4 sites in Central Asia, using standard forensic microscopy to identify prey species. Field identification success varied across study sites, ranging from 21% to 64% genetically confirmed snow leopard scats. Our results confirm the importance of large ungulate prey for snow leopards. Studies that fail to account for potentially commonplace misidentification of snow leopard scat may mistakenly include a large percentage of scats originating from other carnivores and report inaccurate dietary assessments. Relying on field identification of scats led to overestimation of percent occurrence, biomass, and number of small mammals consumed, but underestimated values of these measures for large ungulates in snow leopard diet. This clarification suggests that the conservation value of secondary prey, such as marmots (Marmota spp.) and other small mammals, may be overstated in the literature; stable snow leopard populations are perhaps more reliant upon large ungulate prey than previously understood. © 2016 The Wildlife Society.